Penerapan Buku Ilustrasi Mengenai Saham Sebagai Media Edukasi Untuk Dewasa Muda - Maitri Putri Setiawan (VisArt: Jurnal Seni Rupa dan Design, 2025)
Financial literacy among young adults remains relatively low, particularly in understanding stock investment as an important instrument for achieving long-term financial independence. The lack of accessible and engaging educational resources often leads individuals aged 18–25 to fall into misleading information, make speculative decisions, or become influenced by instant investment schemes. This study aims to design an illustrated book about stocks as an educational medium that is not only visually attractive but also able to present complex financial information in a simple and understandable manner. A descriptive qualitative method was employed through interviews with stock experts and illustrators as well as literature studies related to financial literacy, visual education, and creative learning media. The design results show that the use of illustrations, clear typography, and storytelling techniques effectively simplify stock concepts while increasing young readers’ interest. The book also provides practical guidance on wise investment strategies, risk awareness, and the development of a long-term financial mindset. Therefore, this illustrated book is expected to improve financial literacy and encourage young adults to begin investing with better knowledge and confidence.